Pengembangan Buka Tutup Pintu Rumah Menggunakan Fingerprint - Romi Mulyadi; Nadia Angelin (Pusat Riset dan Inovasi Nasional, 2024)
The large number of poverty and unemployment rates in Indonesia is a trigger for crime, especially theft of valuables in the house. The number of incidents of crime involving theft of rights/property without the use of violence during the 2012–2016 period tends to increase, in 2012 there were 122,777 cases, in 2013 There were 123,133 cases, in 2014 there were 117,751, cases in 2015 decreased to 114,013, cases in 2016 increased to 120,026, cases and in 2017 there were 107,042 cases. This can happen due to negligence, the environment and the security of house doors that still use manual locks. This research will design a security system for opening and closing house doors using fingerprints, so that house doors can only be accessed via the user's fingerprint registered in the microcontroller memory, if the fingerprint the finger is not registered then an alarm will sound, based on testing the tool for fingerprint reading, the fingerprint can be read within 3 to 4 seconds.